2011
DOI: 10.1021/jf201380u
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Lactones in Sweet Cream Butter Oil

Abstract: Sweet cream butter oil was analyzed to identify new volatile compounds that may contribute to its flavor, with an emphasis on lactones. The volatile part of butter oil was obtained by using short-path distillation. As some previously unknown lactones were detected in this first extract, it was fractionated further. The fatty acids were removed, and the extract was fractionated by flash chromatography. Three lactonic fractions possessing a creamy, buttery, and fatty character were investigated in depth by gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The other important contributors of volatiles in butter were lactones formed by hydrolysis and cyclisation of hydroxy-fatty acid triglycerides (Nursten 1997;Sarrazin et al 2011). δ-caprolactone, δ-octalactone and δ-decalactone were identified in butter samples (Table 3).…”
Section: Analysis Of Volatile Compoundsmentioning
confidence: 99%
“…The other important contributors of volatiles in butter were lactones formed by hydrolysis and cyclisation of hydroxy-fatty acid triglycerides (Nursten 1997;Sarrazin et al 2011). δ-caprolactone, δ-octalactone and δ-decalactone were identified in butter samples (Table 3).…”
Section: Analysis Of Volatile Compoundsmentioning
confidence: 99%
“…Compounds that have typically (Sarrazin, Frerot, Bagnoud, Aeberhardt, & Rubin, 2011;Wadodkar et al, 2002) been found in milkfat (associated with fat degradation via oxidation and lipolysis) are shown on the left side of Fig. 3.…”
Section: Qualitative Comparisons Of Gheementioning
confidence: 99%
“…As an alternative, short-path distillation was applied to butter oil and some new lactones were identified 23 .…”
Section: Introductionmentioning
confidence: 99%